2017
DOI: 10.1155/2017/7018393
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia/Reperfusion Injury following Acute Myocardial Infarction: A Critical Issue for Clinicians and Forensic Pathologists

Abstract: Acute myocardial infarction (AMI) is a leading cause of morbidity and mortality. Reperfusion strategies are the current standard therapy for AMI. However, they may result in paradoxical cardiomyocyte dysfunction, known as ischemic reperfusion injury (IRI). Different forms of IRI are recognized, of which only the first two are reversible: reperfusion-induced arrhythmias, myocardial stunning, microvascular obstruction, and lethal myocardial reperfusion injury. Sudden death is the most common pattern for ischemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
232
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(244 citation statements)
references
References 184 publications
(192 reference statements)
1
232
0
Order By: Relevance
“…2) Ischemia reperfusion injury, in which the outbreak of ROS plays an important role, not only causes irreversible myocardial necrosis but also induces cardiomyocyte apoptosis. 3) ROS can be direct cytotoxicity or may pose potential risk of cell death by transforming into free radicals that react with macromolecules, DNA, proteins and lipids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) Ischemia reperfusion injury, in which the outbreak of ROS plays an important role, not only causes irreversible myocardial necrosis but also induces cardiomyocyte apoptosis. 3) ROS can be direct cytotoxicity or may pose potential risk of cell death by transforming into free radicals that react with macromolecules, DNA, proteins and lipids.…”
Section: Discussionmentioning
confidence: 99%
“…1) Although restoration of blood flow to the ischemic heart tissues is important, it is not adequate because myocardial ischemic damage is progressively developed following reperfusion due to an over-production of a large number of biospecies. 2,3) Compelling evidence demonstrated that free radicals generated during ischemia and reperfusion play pivotal roles in myocardial apoptosis. Free radical scavengers can effectively inhibit myocardial apoptosis.…”
mentioning
confidence: 99%
“…Tenzymatic activity of ALDH2 was determined by detecting the transformation from NAD + to NADH, as described. 2 After collecting and quantifying protein, 50 μg of total protein was added to 33 mmol/L sodium pyrophosphate buffer (pH 9.5) containing 0.8 mmol/L of NAD + and 15 μmol/L of propionaldehyde at 25°C. ALDH2 activity was measured in 33 mmol/L sodium pyrophosphate, and 0.1 mL proteins extract.…”
Section: Aldh2 Enzymatic Activitymentioning
confidence: 99%
“…The recovery of blood flow after ischaemia exacerbates tissue and organ injuries, which is known as ischaemia/reperfusion (I/R) injury . Myocardial I/R injury is a complicated pathophysiological phenomenon commonly appeared after ischaemia heart surgery and heart disease .…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 3.8 million men and 3.4 million women die from CHD every year (1)(2)(3). Myocardial ischemia/reperfusion injury is a severe pathological change associated with CHD, which leads to a reduction in heart ejection fraction and causes cardiac decompensation (4). Inhibition of apoptosis to prevent myocardial ischemia/reperfusion injury has long been a therapeutic target (5).…”
Section: Introductionmentioning
confidence: 99%